2022
DOI: 10.36348/sjm.2022.v07i05.004
|View full text |Cite
|
Sign up to set email alerts
|

Tetanus Toxoid Vaccination Status of Women in Baghdad

Abstract: Background: Immunization remains one of the paramount public health interventions and a cost effective method to reduce both the ailment and death associated with infectious diseases. Uptake of vaccination is dependent not only on providing of the vaccination services but also on other influences including awareness and practice of women. Objectives: To assess tetanus toxoid immunization status of mother’s. In addition, to address the factors influencing their immunization status. Method: Cross sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Our study found that women who read newspapers or magazines and those who listened to radio were more likely to receive adequate tetanus toxoid vaccination compared to those who did not. This finding is congruent with previous studies that noted the influence of mass media on women’s uptake of tetanus toxoid uptake [ 25 , 42 , 50 52 ]. Women who were exposed to mass media, except for watching television might have received information on the benefits of tetanus toxoid vaccine, which could have subsequently influenced their decision to take the vaccine [ 53 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study found that women who read newspapers or magazines and those who listened to radio were more likely to receive adequate tetanus toxoid vaccination compared to those who did not. This finding is congruent with previous studies that noted the influence of mass media on women’s uptake of tetanus toxoid uptake [ 25 , 42 , 50 52 ]. Women who were exposed to mass media, except for watching television might have received information on the benefits of tetanus toxoid vaccine, which could have subsequently influenced their decision to take the vaccine [ 53 ].…”
Section: Discussionsupporting
confidence: 93%
“…This finding corroborates with previous studies that found higher likelihood of tetanus toxoid vaccination uptake among women who were employed or working [ 17 , 40 , 41 ]. The financial earnings of working women could have empowered them with the purchasing power to afford transportation to the facility and cost of health services in situations where the services were not entirely free or not covered by health insurance [ 26 , 40 , 42 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…[12,22,23] Furthermore, joint health decision of pregnant women with their husbands, the decision maker related to health issues, distance from health facilities, and fear of side effects are determinants impact vaccination utilization. [25] Obstetrics' history of the pregnant women as (gravidity, age at childbearing, parity, mode of previous delivery, duration of current pregnancy, time of the initial antenatal visit, place of antenatal care, number of antenatal visits, reasons for antenatal visits and the decision maker related to health issues) can also be determinants for tetanus toxoid vaccination use. [26] Knowledge about tetanus and tetanus toxoid vaccination is a crucial determinant of tetanus toxoid vaccination use among pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, maternal immunization with TT-containing vaccines is a cornerstone in preventing both maternal and neonatal tetanus (Islam et al, 2022). It is crucial for pregnant women to receive the TT vaccine to ensure immunity against tetanus for both themselves and their newborns (Shaikh, 2022;Jamil et al, 2022).…”
Section: Introductionmentioning
confidence: 99%